Determinants of user's satisfaction in health plan services - Guimarães Júnior, Djalma Silva; Medeiros, Denise Dumke de (Revista Gestão da Produção Operações e Sistemas, 2020)
New standards for supplementary health services have been introduced in Brazil by the regulatory agent in order to raise the level of user satisfaction. In this context, understanding the critical factors for user satisfaction can help a supplemental healthcare enterprise to add value to its services, expand its customer base, and become more competitive. The purpose of this article is to propose a logistic regression model to estimate the factors that determine the satisfaction of health plan users. The model was created from a consumer survey data. The research results put in evidence the critical role of factors associated with operations management to improve user satisfaction, considering that the significant variables of the model were: physical facilities of the hospital, appointment marking system and number of hospitals agreed with the health plan.